Dispositional Empathy and Perceived Caregiver-Child Interactions in Early Childhood Care and Education: Examining the Moderating Effects of Age and Personality - Aboagye-Acquaah, R.O. (University of Ghana, 2016)
Although various studies have established a relationship between dispositional empathy and caregiver-child interactions, the influences of the individual dimensions of dispositional empathy have not been adequately explored among caregivers in the early childhood care and education (ECCE) setting. The current study examined how the empathic dispositions of ECCE caregivers in the Ghanaian setting influenced their beliefs and intentions about their interactions with the children in their care, while controlling for training, years of experience, job commitment and satisfaction with salary. The moderation effects of age and three personality dimensions on the relationship between caregivers‟ dispositional empathy and their perceived interactions with the children were also examined. The study design was a cross-sectional survey, which involved 154 participants, who were ECCE caregivers within the Ga East District in the Greater Accra region of Ghana. The stratified random sampling technique was used to select participants. The results indicated that perceived caregiver-child interaction (PCCI) was positively predicted by empathic concern and perspective-taking and negatively predicted by personal distress. Empathic concern accounted for the highest variance in caregivers‟ perceived interactions with the children. Additionally, neuroticism significantly moderated the relationship between dispositional empathy and perceived caregiver-child interactions. The implications of the findings on both theory and practice are discussed in the context of ECCE, and recommendations made for future research.
Theses (MPhil.) - University Of Ghana, 2016
Keywords: Dispositional Empathy; Perceived Caregiver-child Interactions; Early Childhood; Care and Education; Age; Personality